Pengaruh Pendapatan dan Jumlah Anggota Keluarga Terhadap Kesejahteraan Buruh Petik Cengkeh di Desa Selat, Buleleng - Luh Nenik Cahayu Yuni Aristin; Made Ary Meitriana (Universitas Pendidikan Ganesha, 2025)
This research aims to determine (1) the effect of income, (2) the number of family members, and (3) the welfare of clove pickers in Selat Village, Buleleng. The population for this study consists of clove pickers in Selat Village, Buleleng, totaling 110 workers based on data from Selat Village in 2023, with a sample size of 86 people. The data collection method used a questionnaire and was analyzed using multiple linear regression analysis. Hypothesis testing was conducted using the t-test, F-test, and coefficient of determination test, processed with the help of SPSS version 25. The results of this study indicate that (1) income has a positive and significant effect on the welfare of clove pickers in Selat Village, Buleleng, (2) the number of family members has a positive and significant effect on the welfare of clove pickers in Selat Village, Buleleng, (3) income and the number of family members have a positive and significant effect on the welfare of clove pickers in Selat Village, Buleleng. Overall, the income and number of family members contribute to welfare by 21.6%, and the remaining 78.4% is influenced by other variables that were not studied.